Transition corner structure optimization and ultimate bearing capacity evaluation of marine pressure cabin: experiment and numerical analysis. (January 2023) - Xu, Shuangxi; Zhang, Shichen; Chen, Jing; Wang, Ning; Shen, Wei; Cai, Yao; Tang, Weiguo
Abstract: With the improvement of ship pollutant emission requirements, LNG (liquefied natural gas) market demand is growing strongly. The bearing capacity requirements of pressure vessels are getting higher and higher, and the optimal design of corner structures becomes the key to bearing capacity. However, in order to improve the volume ratio, traditional LNG prismatic pressure vessels usually adopt right-angle corners, and there is obvious stress concentration at the corners. In order to optimize the corner structure and improve the ultimate bearing capacity, based on similarity theory, the ultimate bearing tests on pressure vessels with four improved corners are carried out, and the corresponding numerical simulation and parametric analysis are further developed. According to the calculation results, it is found that the finite element calculation results are in good agreement with the test results. Through the establishment of four full-scale numerical models with different corners, the lightweight effect and ultimate bearing capacity are further obtained, which provides quantitative reference for the design of non-cylindrical LNG storage containers. The results show that the corner form of inclined plate is a relatively good corner form of pressure-resistant structure. Highlights: The ultimate bearing tests on pressure vessels with arc corner, inclined plate corner, right angle corner and inclined plate plus right angle corner are carried out. By establishing four full-scale numerical models with different corner forms, the lightweight effect and ultimate bearing capacity are obtained. The ultimate bearing test verify the effectiveness of numerical method.